Factors that determine the demand for family Takaful: evidence from Malaysia - Jamawi, Busyra (2014)
This study attempts to determine the determinants for Family Takaful consumption, whether income, price of Family Takaful and interest rate related to the demand for Family Takaful. An interest in understanding the factors behind the purchase of life insurance has been growing since the first empirical study on the subject was conducted by Hammond et al. (1967). This empirical study focuses on 100 respondents who are working in several sectors. Using the survey approach, the findings showed that individual income, price of Family Takaful (premium) and interest rate have significant relationships with the demand for Family Takaful in Malaysia. The findings of this paper will provide important information for the insurers and policy makers to formulate new policies and strategies to further develop and promote the insurance industry.